2017
DOI: 10.19082/5472
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis among hypertensive patients in King Abdulaziz University (KAU) Hospital, Jeddah, Kingdom of Saudi Arabia

Abstract: BackgroundDeep venous thrombosis (DVT) is a frequent cardiovascular disorder. It is among the main causes of morbidity and mortality among hospitalized patients and, at the same time, can be easily avoided. Studies clarified that there are a variety of factors which can be significantly associated with the development of DVT in hospitalized patients.Objectiveto identify frequency and factors associated with occurrence of DVT among hypertensive patients referred to KAU hospital, Jeddah, Kingdom of Saudi Arabia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…In terms of hypertension, its association with the development of DVT is a controversial issue. Some previous studies suggested that hypertension could increase the risk of DVT6, but some other studies concluded that there was no statistically significant association between it and DVT 15. However, in the current study, we confirmed that hypertension was an independent risk factor for DVT in patients with gynecological malignant tumor.…”
Section: Discussionsupporting
confidence: 70%
“…In terms of hypertension, its association with the development of DVT is a controversial issue. Some previous studies suggested that hypertension could increase the risk of DVT6, but some other studies concluded that there was no statistically significant association between it and DVT 15. However, in the current study, we confirmed that hypertension was an independent risk factor for DVT in patients with gynecological malignant tumor.…”
Section: Discussionsupporting
confidence: 70%
“…Second, our cases were mostly obese or overweight (BMI ranged from 20.1 to 39.8 with a mean of 28.16 ± 4.90 kg/m2), which has been linked to an increased risk of PE in previous studies [13] . Thirdly, the presence of a high incidence of smoking (40%) in our cases is a risk factor for the development of thromboembolic events [14] , in addition to the controversial roles of high incidences of hypertension and diabetes (72% and 32%, respectively) [15] . Lastly, the possible late presentations and lack of resources for diagnosis and management may have a role in this high incidence of embolic complications in our patients.…”
Section: Discussionmentioning
confidence: 67%
“…The higher incidence of UEDVTs in patients with PICC lines, as opposed to central venous lines, may be explained by the fact that PICC lines traverse a longer route through the venous system and have a higher catheter:vein-diameter ratio than central lines, all increasing hypercoagulability. 11 What was interesting to see was that while PICC lines and CVCs posed significantly increased risk of developing UEDVT, patients with implanted pacemakers or cardiac implantable electronic devices did not have an increased risk of developing UEDVT ( p =0.181). This could be explained by the varying approaches to implanting such devices (either endovascularly or surgically) and the fact that a shorter vein is disturbed with endovascular placement compared to central lines or PICC lines, decreasing the risk of thrombus development.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the varying approaches to implanting such devices (either endovascularly or surgically) and the fact that a shorter vein is disturbed with endovascular placement compared to central lines or PICC lines, decreasing the risk of thrombus development. 11 …”
Section: Discussionmentioning
confidence: 99%